FEASIBILITY OF BAY SALAM FINANCE: A SURVEY OF THE OPINIONS OF STAKEHOLDERS - Muhammad Tahir Manoori; Atiq-ur-Rehman Atiq-ur-Rehman; Muhammad Jamil; Muhammad Ishfaq (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2018)
The present study aims to explore the potential application of Bai Salam (forward sale agreement) as substitute financial instrument in the agriculture sector of Pakistan. The conclusion is drawn through a survey questionnaire from 300 farmers and bankers in a district of Punjab. For analysis, we use SPSS software and presented the results by using descriptive methods. This study overall concludes the banker’s and farmer’s awareness, willingness, risks, hurdles and the role of institutions in the Salam promotion. The majority of the farmers are not aware of the Salam contract because the Islamic bank’s branch network is limited to urban areas and there is no proper promotion campaign launched by the Islamic banks for awareness about Salaam among the farmers. Bankers are reluctant to finance the tenants, orchards due to more operational risk for the bank. Bankers opinion that small farmers do not have personal securities which is not a solid reason because half of the sampled farmers take a loan from the formal system if they can provide securities to conventional interest-based institution why they can’t provide securities to Islamic financial institutions? There is a vast market for the Islamic Banks if they sincerely pay their attention towards forward sale contracts. The concept applies to all areas of agriculture and livestock farming to overcome financing problems and boost production.